2018
DOI: 10.1021/acs.jpca.8b07276
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Cs Adsorption on Montmorillonite Clay from 133Cs Solid-State NMR and Density Functional Theory Calculations

Abstract: The adsorption sites of Cs on montmorillonite clays were investigated by theoretical 133Cs chemical shift calculations, 133Cs magic-angle-spinning nuclear magnetic resonance (MAS NMR) spectroscopy, and X-ray diffraction under controlled relative humidity. The theoretical calculations were carried out for structures with three stacking variations in the clay layers, where hexagonal cavities formed with Si–O bonds in the tetrahedral layers were aligned as monoclinic, parallel, alternated; with various d-spacings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
(77 reference statements)
5
10
0
Order By: Relevance
“…The doping of paramagnetic Yb 3+ and Er 3+ ions induces a shift of the 133 Cs peak from 103.3 to 101.1 ppm as well as a significant broadening of this signal (the full-width-athalf-height increases from 173 to 300 Hz) ( Figure 1d). [42,43] The shift of peak position is due to the delocalization of extra electron density of Yb 3+ and Er 3+ (spin I = 1/2 and 3/2) on Cs + , that is, the Fermi-contact interaction. The broadening of NMR peak corresponds to the accelerated transverse (T 2 ) relaxation of 133 Cs in the presence of adjacent paramagnetic Yb 3+ and Er 3+ ions, resulting from the strong dipolar coupling between unpaired electrons and 133 Cs nuclei (i.e., the pseudo-contact interaction).…”
mentioning
confidence: 99%
“…The doping of paramagnetic Yb 3+ and Er 3+ ions induces a shift of the 133 Cs peak from 103.3 to 101.1 ppm as well as a significant broadening of this signal (the full-width-athalf-height increases from 173 to 300 Hz) ( Figure 1d). [42,43] The shift of peak position is due to the delocalization of extra electron density of Yb 3+ and Er 3+ (spin I = 1/2 and 3/2) on Cs + , that is, the Fermi-contact interaction. The broadening of NMR peak corresponds to the accelerated transverse (T 2 ) relaxation of 133 Cs in the presence of adjacent paramagnetic Yb 3+ and Er 3+ ions, resulting from the strong dipolar coupling between unpaired electrons and 133 Cs nuclei (i.e., the pseudo-contact interaction).…”
mentioning
confidence: 99%
“…The second-order quadrupolar interaction affects the line shape of the 133 Cs MAS NMR spectra, meaning that the peak position is not consistent with δ iso . However, the small quadrupole moment of 133 Cs leads to a negligibly small second-order quadrupolar interaction, allowing the determination of δ iso at the peak position …”
Section: Solid-state 133cs Nmrmentioning
confidence: 99%
“…These structural differences can be identified by the coordination number inferred from the EXAFS spectra of adsorbed cations. In addition, adsorption sites in the nanopore space, which are formed by a layer mismatch or defects in the crystal structure, form new adsorption sites within the system. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong interactions between the Cs ion and clay minerals have been widely studied through field studies, , laboratory experiments, and computational studies. One study demonstrated the formation of the frayed edge site in the interlayer space caused by the insertion and subsequent dehydration of the hydrated Cs ion. It is one of the essential preconditions for the promotion of strong interaction between Cs and clay, apart from the interaction between the Cs ion and basal and edge surfaces .…”
Section: Introductionmentioning
confidence: 99%